Effect of Bio based rejuvenator on Rutting Performance of Aged Bitumen - Ahmad, Kabiru Abdullahi; Abdullah, Mohd Ezree; Nda, Muhammad; Usman, Nura; Abdul Hassan, Norhidayah (International Journal of Integrated Engineering, 2019)
Rutting has been and continues to be a problem in performance of asphalt mixes. The purpose of this paper is to provide a summary of studies on effect of bio based rejuvenator on rutting performance of aged asphalt. Â Aged asphalt binder incorporating different percentage of bio-based rejuvenator extracted from jatropha curcas (jco) was evaluated to investigate the effect of the rejuvenator content on rutting deformation of rejuvenated aged asphalt binders The findings shows that, the addition of bio based rejuvenator affects the rutting performance of aged binder. The results of rutting evaluation from rheological analyses of aged and blended binders indicate that the characteristics of blended binders are dependent on bio-based rejuvenator (jco). The results show that the complex modulus decreases with the increase in temperature which corresponds to a decrease in loading frequencies.